Tipos de acoso escolar entre pares en estudiantes de un colegio de carácter oficial ubicado en la ciudad de Cali - Villavicencio Ramírez, María Erika (Universidad Antonio Nariño, 2022)
The objective of this study was to describe the most frequent types of bullying among peers, students in grades 7, 8, and 9, of a school in the city of Cali. Based on the literature review, it was found that the phenomenon of bullying is an issue that has become visible over the years, since, with the various studies it has been possible to identify the main types of bullying, the actors involved in this act and the causes, all of which has led educational entities to intervene from prevention. However, at present it seems that this behavior among peers has increased. That is why the purpose of this research was to give an account of the current state on the subject of bullying, describing the most frequent types of bullying among peers, students in grades 7, 8, and 9, of a school in the city of Cali. This study was conducted through quantitative research methodology, with a descriptive scope, it is nonexperimental since no variables were deliberately manipulated.